The iceman - Vromen, Ariel; Shannon, Michael, 1974-; Ryder, Winona, 1971-; Franco, James, 1978-; Mazar, Haim; Bruno, Anthony (Los Angeles, CA : Millennium Entertainment, 2013)
A fictionalized account of the story of Richard Kuklinski, a notorious hitman for the New Jersey Mafia, nicknamed the "Iceman" for his practice of freezing his victims' bodies so as to confuse the time of death.
Originally released as a motion picture in 2012.
Based on the book "The iceman : the true story of a cold-blooded killer" by Anthony Bruno and the documentary "The iceman tapes : conversations with a killer."
Wide screen 1.66:1.
Features: making of, behind the scenes.
Camera, Bobby Bukowski ; production designer, Nathan Amondson ; editor, Danny Rafic ; music, Haim Mazar.
Michael Shannon, Winona Ryder, James Franco, Ray Liotta, Chris Evans.
Keywords: Kuklinski, Richard -- Drama; Bruno, Anthony -- Film adaptations; Serial murderers -- Drama; Organized crime -- Drama; Fiction films; Thriller films; Based on the book; Feature films; Biographical films